A randomized controlled trial of the effects of vitamin D supplementation on arterial stiffness and aortic blood pressure in Native American women. Issue 2 (June 2015) - Gepner, Adam D.; Haller, Irina V.; Krueger, Diane C.; Korcarz, Claudia E.; Binkley, Neil; Stein, James H.
Abstract: Objective: It is unclear if vitamin D supplementation improves central blood pressure or arterial stiffness in Native American (NA) women. Methods: Healthy postmenopausal NA women were randomized to receive 400 IU or 2500 IU of vitamin D for 6 months. Central systolic blood pressure (cSBP), central pulse pressure (cPP) and aortic augmentation index (AIx) were estimated by tonometry at baseline and after 6 months. Results: Study volunteers (n = 98) were 61 (7.3) years old. 25(OH)D was 26.4 (11.0) ng/mL. 25(OH)D was similar between the two treatment groups (p = 0.291), as were baseline cSBP, cPP, and CVD risk factors (all p > 0.1). Treatment with 2500 IU of daily vitamin D3 did not affect cSBP, cPP, or AIx (all p > 0.1) compared to 400 IU daily. Conclusions: Despite low serum 25(OH)D at baseline, 6 months of vitamin D supplementation did not improve central blood pressure parameters or arterial stiffness in NA women. Clinical trials. gov identifier: NCT01490333 .